COLOUR THEREPY-BOON TO MANKIND - Mathew, Sajan Kurien (International Journal of Research -GRANTHAALAYAH, 2014)
Colour Therapy is a complementary therapy for which there is evidence dating back thousands of years to the ancient cultures of Egypt, China and India. Colour is simply light of varying wavelengths, thus each colour has its own particular wavelength and energy. "Colour affects our life. Colour is physical..........we see it. Colour communicates............we recieve information from the language of colour. Colour is emotional..........it evokes our feeling."